Biopreservation potential of lactic acid bacteria from Andean fermented food of vegetal origin. (August 2017) - Yépez, Alba; Luz, Carlos; Meca, Giuseppe; Vignolo, Graciela; Mañes, Jordi; Aznar, Rosa
Abstract: Microbial fermentations have long represented a way of natural biopreservation of raw materials, which frequently originated new food products. Among them, traditionally fermented products still manufactured by native populations all around the world are source of lactic acid bacteria (LAB) strains with high biotechnological potential. LAB are food grade microorganisms and therefore a good alternative to chemicals to be applied in food preservation. A total of 130 LAB isolates recovered from "chicha" and "tocosh", traditional fermented Andean products of vegetal origin, were screened for antimicrobial activities against spoiler fungi Meyerozyma guilliermondii CECT 1021 (synonym Pichia guilliermondii ), Penicillium roqueforti CECT 2905 NT, Aspergillus oryzae CECT 2094 NT and Aspergillus niger CECT 2807 as well as against foodborne pathogens Escherichia coli O157:H7 CECT 5947, Listeria innocua CECT 910 T and Salmonella enterica subsp. enterica serovar Typhi CECT 4138. LAB isolates represented nine species and four genera that exhibited a general inhibition of food pathogens and were also active against A. oryzae and M. guilliermondii while a poor inhibition of A. niger and P. roqueforti was produced. Antifungal activity of cell free supernatants (CFS) from seven selected strains grown in MRS was confirmed against toxigenic fungi Aspergillus parasiticus CECT 2681, Penicillium expansum CECT 2278 and Fusarium verticilloides CECT 2987 and also on the three foodborne bacteria included in the study. Phenyllactic and 3, 5-Di-O-caffeoylquinic acids were identified as the predominant bioactive compounds in CFS by QuEChERS extraction with LC-MS-LIT detection approach. Four out of seven strains free of antibiotic resistances involving L. plantarum M5MA1 and M9MM1 from chicha and L. fermentum T3M3 and Lc. mesenteroides T1M3 from tocosh showed high potential to be used as biopreservatives in food applications. Highlights: LAB strains from traditional fermented Andean products showed antimicrobial activity. Most LAB strains inhibited the three bacterial pathogens tested in the study. Seven LAB cell free supernatants confirmed inhibition to studied toxigenic fungi. Active compounds were identified by QuEChERS extraction/LC-MS-LIT system. Four strains exhibit potential as biopreservatives in food applications.